1995
DOI: 10.1038/sc.1995.112
|View full text |Cite
|
Sign up to set email alerts
|

Influence of electrical stimulation of the tibialis anterior muscle in paraplegic subjects. 2. Morphological and histochemical properties

Abstract: In adult paraplegic subjects one tibialis anterior muscle received daily electrical stimulation for 4 weeks at twice the motor threshold to determine changes of morphological and histochemical profiles (this paper) and of contractile properties (preceding paperV Bilateral biopsies, obtained 4 weeks before, and immediately after, electrical stimulation, were studied for fibre type proportions, fibre diameters, oxidative capacity, microvascu lature and histopathology, Before stimulation the biopsies showed disus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
109
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(120 citation statements)
references
References 29 publications
11
109
0
Order By: Relevance
“…The results of the present study support and extend the observations of other studies in human subjects.27 , 32 Furthermore, the contractile properties appear to be well matched to the histochemical profiles determined from muscle biopsy, with an increase in the proportion of type 2 fibres, a decrease in fibre diameter and a decrease in the activity of oxidative enzymes, as discussed in the following paper. 1 The paraplegic subjects demonstrated a marked in crease in the half relaxation time index in comparison to normal SUbjects. Lenman et a12?…”
Section: Discussionmentioning
confidence: 92%
“…The results of the present study support and extend the observations of other studies in human subjects.27 , 32 Furthermore, the contractile properties appear to be well matched to the histochemical profiles determined from muscle biopsy, with an increase in the proportion of type 2 fibres, a decrease in fibre diameter and a decrease in the activity of oxidative enzymes, as discussed in the following paper. 1 The paraplegic subjects demonstrated a marked in crease in the half relaxation time index in comparison to normal SUbjects. Lenman et a12?…”
Section: Discussionmentioning
confidence: 92%
“…38 Consistent with this suggestion are studies that have suggested that long term SCI patients have increased fatiging that is not explained by reduced oxidative enzymes. 39,40 In summary, this study is one of the ®rst to examine incomplete SCI, who make up as much as 55% of all SCI patients. These ®ndings suggest that incomplete spinal cord injured patients have impaired vascular control.…”
Section: Discussionmentioning
confidence: 99%
“…Round et al 7 determined that biopsies from the vastus lateralis of patients 11 months ± 9 years post SCI were composed primarily of Type II ®bres. In a recent report by Rochester et al 8,9 patients were studied 1 ± 14 years post SCI. In six of seven patients there was a predominance of Type II ®bres found in biopsies from the tibialis anterior.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the majority of the studies from SCI patients have relied on a relative comparison of the histochemically determined ®bre types between normal and SCI muscle biopsies. 1,2,6,7,9 The subjective nature of ®bre typing based on saturated histochemical reaction products may be suited for muscle under steady state conditions, but is much less reliable under conditions of perturbation. 5,18 Therefore, they may lack the sensitivity required to discern early changes in those properties determining ®bre type.…”
Section: Introductionmentioning
confidence: 99%